ASSESSMENT OF KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING ANTIBIOTIC USE AND RESISTANCE AMONG COMMUNITY PHARMACISTS IN SANA’A (YEMEN) - ADNAN ALADHAL; ALI A. AL-MEHDAR; ALI SALMAN AL-SHAMI; ASMA AHMED ALWAN; ZAID ABDO THAWABA; NAJIB FAISAL AHMED (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aims to assess pharmacists’ knowledge, attitudes, and practices regarding over-the-counter antimicrobial use and antimicrobial resistance. Methods: We conducted a cross-sectional descriptive study using a self-administered questionnaire for pharmacists in Sana’a city, Yemen. Results: An arithmetic mean of 2.5 and a standard deviation of 1.25 rated the level of knowledge among community pharmacists in Sana’a, Yemen, concerning antibiotic use and resistance as low. We rated the attitudes toward antibiotic use and resistance among community pharmacists in Sana’a, Yemen, at a medium level, with an arithmetic mean of 3.18 and a standard deviation of 1.25. In addition, we rated the rate of practices concerning antibiotic use and resistance among community pharmacists in Sana’a (Yemen) as medium, with an arithmetic mean of 2.7 and a standard deviation of 1.08. We observed no notable differences in age, educational level, or years of experience among community pharmacists; however, we identified a significant difference in gender at a level of 0.003. There is no significant correlation between the age, educational level, years of experience, gender, and knowledge variables of community pharmacists. There exists a notable correlation between gender and attitude, alongside a weak inverse correlation between gender and practice variables. Conclusion: Community pharmacists in Sana’a, Yemen, rated their knowledge, attitudes, and practices regarding antibiotic use and resistance poorly, with an arithmetic mean of 2.5 and a standard deviation of 1.25. Community pharmacists in Sana’a, Yemen, assessed their attitudes toward antibiotic use and resistance as moderate, with a mean score of 3.18 and a standard deviation of 1.25. Ultimately, at the 0.05 significance level, there is no statistically significant correlation between the average responses of community pharmacists regarding the research variables (age, educational level, years of experience, gender) and their association with knowledge variables. We observe a statistically significant correlation between the gender variable and attitude, with a significance level of 0.005. A weak inverse correlation exists between gender and practice variables. A statistically significant correlation exists between knowledge and practice.